STRATEGI PENGHINDARAN PAJAK PERUSAHAAN SEBELUM DAN SELAMA MASA PANDEMI - Angelina, Angelina; Margaretha, Margaretha; Budiman, Rivan; Kristanto, Septian Bayu; Hartoni, Hartoni (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This research aims to provide empirical evidence of corporate tax avoidance strategies before and during the COVID-19 pandemic. The tax avoidance strategy predicts from three following factors: thin capitalization, profitability, and company size. Research Method. This study is a quantitative study and data analyzed using panel data regression. To measure tax avoidance, the researcher uses three proxies: ETR, CETR, and BTD. Researchers used 279 samples of manufacturing companies during the 2018-2020 period.Research Result and Findings. The results of the study show differences in the company's avoidance strategies before the pandemic (2018-2019) and during the pandemic (2020). The CETR and BTD proxies show that before the pandemic, company size was used as a tax avoidance strategy. During the pandemic, profitability is used as a tax avoidance strategy. This research has weaknesses in the pandemic period which has only been running for one year, and the scope of the research only has an impact in Indonesia.